Technology transfer and development : (Fund for Multinational Management Education, 1974)
The technology transfer experiences of several countries are examined in the context of these criteria. A theoretical framework that links issues concerning contents of technology transfer with the levels of technological capability is presented. The implications for policies and strategies concerning technology transfer are examined.